2019
DOI: 10.3233/jad-190391
|View full text |Cite
|
Sign up to set email alerts
|

Delirium Predisposing and Triggering Factors in Nursing Home Residents: A Cohort Trial-Nested Case-Control Study

Abstract: Background: Delirium is a common geriatric syndrome, with a prevalence of between 15-70% among older long-term care residents. It is associated with adverse outcomes, and its onset may prove imperceptible to health professionals. Few studies in institutionalized older people have analyzed the predictors of delirium. Objective: The aim of the present study was to identify delirium predisposing and triggering factors, and develop a predictive model. Methods: A cohort trial-nested case-control study covering a pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 53 publications
0
26
0
1
Order By: Relevance
“…From our review, we identified 28 [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] articles with relevant data regarding the prevalence of delirium, and eight articles [ 11 , 26 , 39 , 40 , 41 , 42 , 43 , 44 ] described the incidence of delirium. Total population mean age ranged from 76.2 years to 88.5 years, and 46.8% to 90.8% of the participants in the studies were female.…”
Section: Review Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From our review, we identified 28 [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 ] articles with relevant data regarding the prevalence of delirium, and eight articles [ 11 , 26 , 39 , 40 , 41 , 42 , 43 , 44 ] described the incidence of delirium. Total population mean age ranged from 76.2 years to 88.5 years, and 46.8% to 90.8% of the participants in the studies were female.…”
Section: Review Resultsmentioning
confidence: 99%
“…Parkinson’s disease and depression were other comorbidities reported as risk factors. Of interest, diabetes resulted as a protective risk factor, probably because the frequent glycemic control results in closer contact between nurses and older people, which may avoid the development of delirium [ 41 ].…”
Section: Review Resultsmentioning
confidence: 99%
“…Risk factors of developing postoperative delirium could be patient-related, could be different depending on the timing of appearance during hospitalization, and could be medical-or surgery-related factors [47,48]. More generally, the risk of developing postoperative delirium derives from the presence of some predisposing factors in addition to one or more precipitant factors (Table 1) [46][47][48][49][50].…”
Section: Postoperative Delirium: Epidemiology and Risk Factorsmentioning
confidence: 99%
“…A evicção de fatores de risco de delirium conduz à diminuição direta da ocorrência deste e das suas consequências. 35 Em cerca de 50% dos casos, os quadros de delirium são reversíveis. 25 Assim, os profissionais de saúde, os cuidadores e os familiares dos doentes devem ser treinados para reconhecer atempadamente e alertar para o surgimento de sintomas de delirium.…”
Section: Fisiopatologiaunclassified